Analisis Yuridis-Sosiolegal terhadap Kekerasan Anak Berakibat Kematian: Studi Kasus Anak Berkonflik dengan Hukum di Palembang - Toto Hardiyanto; Ulfa Rika; Tommi Prayoga (CV. Era Digital Nusantara, 2026)
Violence involving children that results in death raises a complex legal and sociolegal problem because the alleged perpetrator, victim, and several witnesses may all be children. This article analyzes the factual construction, legal qualification, and child protection implications of a case of alleged child-on-child violence in Palembang, Indonesia. The study applies normative legal research combined with a qualitative case study design. The sociolegal dimension is examined through an anonymized police case resume and supporting literature, not through direct field interviews. Data were analyzed by chronological reconstruction, legal element mapping, thematic coding, and statutory, case-based, and conceptual interpretation. The case file indicates that the incident began with peer-group conflict facilitated by digital communication, escalated into physical fighting, involved a sharp weapon, and resulted in the death of a child victim. The alleged conduct is relevant to Article 76C in conjunction with Article 80 paragraph (3) of the Child Protection Law, while the process must remain consistent with the Juvenile Criminal Justice System Law. Serious juvenile violence must be analyzed as both a criminal event and a failure of the child-protection ecosystem. Legal certainty, victim recovery, child offender rehabilitation, child witness protection, and early prevention of peer-group violence need to be balanced.